Uji Efektivitas Prototype MABOA (Magic Briket Oil Absorbent) sebagai Mitigasi Pencemaran Minyak di Lingkungan Perairan - Nur Sakinah Junirahma; Mauliddiana Nurul Ilyas; Muhammad Alfian Arifin; Romi Dwi Nanda (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Pollution of hydrocarbons in marine waters was recorded up to 2003 around 6.44 million tons and dominant due to the results of fishery port activities to cause the balance of coastal ecosystems disrupted. The drained state funds for its handling can reach 1000 USD per ton up to 33,000 USD in each region. Various efforts have been made is still not effective enough. The purpose of this program is to get the appropriate technology design in overcoming the problem of hydrocarbon pollution in the fishing port. The method used by literature and field study and a series of testing tools. The solution is called MABOA (Magic Briquette Oil Absorbent) is a technology that is applied aplikatif appropriate to overcome the problem of oil pollution in the port area. This tool is a net with the main components of magic briquettes, auto-spray containing bacteria degradation and microcontroller which as a whole has the ability to absorb and degrade hydrocarbon compounds. The circular MABOA net will prevent the expansion of the oil spill zone by the absorption process by magic briquettes. Pseudomonas puttidae and Bacillus sp. In auto-spray will be automatically sprayed over the surface of the spill zone to perform the decomposition of hydrocarbon compounds. Bacteria will grow and utilize hydrocarbons that have been absorbed and accumulated in the body of magic briquettes so that the cleaning process becomes more effective and faster. Results from a series of trials showed that MABOA with 3meter diameter dimension able to absorb hydrocarbon compound as much as 35.000mL with 3-5min time absorption rate and with density of colonies of bacteria 3,5x109 able to degrade 32% of existing hydrocarbon compound with efficiency time 3-7 days. The data is an accumulation of those component test result data.